Pressure transient analysis of multistage fractured horizontal wells based on detailed characterization of stimulated area - Wang, Huzhen; Liu, Tiancheng; Sun, Zhuangzhuang; Wang, Chunyao; Zhang, Yangang; Chen, Yulin; Liu, Zhenyu; Zhou, Zhijun (Frontiers in Energy Research, 2023)
In ultralow permeability tight oil reservoirs, the fracturing scale of multistage fractured horizontal wells (MFHWs) is relatively large, and the artificial fracture system is generally more complex. Analytical and semi-analytical methods are difficult to characterize the stimulated area in detail, which includes main fractures, branch fractures, and microfractures. Numerical methods have unique advantages in studying such problems. The mathematical model of oil–water two-phase seepage is established by the finite element method, the permeability and pseudo threshold pressure gradient that vary with spatial position are proposed to characterize the stimulated area except the main fracture. A single well numerical model was established to study the influence of the width and permeability of the stimulated area on the pressure response. The analysis shows that the transient pressure response of MFHW is controlled by main fracture conductivity. Main fractures have high conductivity can better communicate the stimulated area, and MFHW can be better developed.